Optimization of Lot Sizing Technique in Determining the Best Supplier of Local and Imported Beef Supply with Simple Additive Weighting (SAW) Method - Budi Susanto; Nuri Kartini; Pahla Widhiani; Harry Gunawan (Jurnal Penelitian Pendidikan IPA, 2025)
It is important for companies engaged in the food processing industry to determine the right amount and time of ordering so that raw materials are available optimally. The purpose of this research is to measure lot sizing optimization in determining the best supplier of local and imported beef supplies using Simple Additive Weighting (SAW). The data used is local and imported beef raw material data at PT Uutbeef Indonesia Storage (Warehouse Storage) Cirebon Regency Jawabarat. The results of the study for Johndee and Amroon meat type products using the Lot For Lot (LOL) lot sizing technique obtained the lowest cost with the total cost generated was IDR 35,832,654,000 compared to using lot sizing Economic Order Quantity (EOQ), or Period Order Quantity (POQ). The results of the weighting of supplier criteria, the preference value of the maroon supplier obtained the best results for PT Sarana Inti with a value of 0.92 and for the preference of the johndee supplier obtained the best results, namely PT Sinar with the final result of 0.93. Therefore, Lot Sizing optimization can be used by companies to overcome problems regarding the quantity, time and cost of inventory, so as to reduce the excess raw materials that occur, ensure smooth production and increase the productivity and profitability of the company